The Relationship between Organizational Justice and Quality Performance among Healthcare Workers: A Pilot Study. (3rd April 2014) - Mohamed, Salwa Attia
Abstract : Organization justice refers to the extent to which employees perceive workplace procedure, interactions, and outcomes to be fair in nature. So, this study aimed to investigate the relationship between organizational justice and quality performance among health care workers. The study was conducted at the Public Hospital in Fayoum, Egypt. The study included a convenience sample of 100 healthcare workers (60 nurses and 40 physicians) that were recruited. Tools used for data collection included (1) questionnaire sheet which is used to measure health workers' perception of organizational justices. It includes four types: distributive, procedural, interpersonal, and informational justice. (2) Quality performance questionnaire sheet: this tool was used to examine health workers' perception regarding their quality performance. It contained three types: information, value, and skill. The results revealed that a positive correlation was found between organizational justice components and quality performance among the various categories of health workers' perception ( P ≤ 0.05 ) . It has been recommended to replicate the study on a larger probability sample from different hospital settings to achieve more generalizable results and reinforce justice during organization of ministry centers in Egypt.